Qanilaarneq (Closeness/Being Close) as a Desired State: Mediating Conflict Through Storytelling in Kalaallit Nunaat (Greenland) - Chahine, Anne (Études Inuit Studies, 2023)
This paper focuses on storytelling as a site for knowledge creation and meaning making to better understand how relationships are established and community is made in Kalaallit Nunaat (Greenland). The basis of this article is a selection of stories created by young Kalaallit (Greenlandic Inuit) adults as part of a research project engaging in future memory work, where participants were asked to create “future memories” for subsequent generations by producing stories that best represent what they consider to be worth preserving. Connecting these stories are the storytellers’ evocations of solidarity, care, and responsibility, gesturing to other members of the Kalaallit community. Rather than centering on the stories’ content, I conceptualize their intent through a focus on storytelling as a social activity. I argue that the young Kalaallit I worked with seek to mediate conflict and mend rifts in society through their storytelling practice, envisioning a future state of Kalaallit community relations that is “closer” in nature, and I propose the Kalaallisut term “qanilaarneq” (closeness/being close) as a metaphor to think with and make this notion more tangible.